Characteristics associated with career self-reliance behaviors of nurses working in nursing homes in Japan: A cross-sectional study - Nakayama, Ayako; Hoshino, Junko; Hotta, Masashi; Hashimoto, Mayuri; Furukawa, Naomi (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: With an aging global population, establishing integrated systems for long-term care is challenging in several countries. Adequate and quality service for older adults in nursing homes can improve their quality of life. The career self-reliance of nurses working in nursing homes may affect the quality of life of older adults; this suggests a need for educational support for career self-reliance behavior. Objective: Our study aimed to identify characteristics associated with the career self-reliance behaviors of nurses working in nursing homes. Methods: Data were collected from nurses working in 789 nursing homes in Japan using questionnaires in 2018. The questionnaire consisted of the Scale of Career Self-Reliance Attitude, Career Self-Reliance Behavior to measure the degree of nurses’ career self-reliance, questions about personal attributes, work environment, and work commitment; and the Clinical Nursing Competence Self-Assessment Scale. A multiple regression analysis was conducted using career self-reliance as the dependent variable and characteristics as the independent variables. Results: Consequently, a total of 336 questionnaires were collected, of which 289 without missing data were analyzed. Of the 289 participants, 79 (27.3%) had certifications or licenses other than those for nursing or had completed graduate school. As a result of multiple regression analysis, a higher frequency of nursing practice (β = 0.38, p <0.001) was associated with career self-reliance attitudes. Having certifications or licenses other than those for nursing or completing graduate school (β = 0.11, p = 0.03), job satisfaction as a nurse (β = 0.12, p = 0.03), higher frequency of nursing practice (β = 0.28, p <0.001), and a higher degree of career self-reliance attitude (β = 0.45, p <0.001) were associated with career self-reliance behavior. Relationships with supervisors or colleagues were not associated with career self-reliance. Conclusion: It is important for nurses working in nursing homes to enrich their nursing practice, continue learning, and be satisfied with their jobs to improve their career self-reliance. Nurses and administrators working in nursing homes should make efforts to obtain these characteristics for nurses’ career self-reliance behaviors. Particularly, maintaining nursing practice frequency is essential for improving the quality of life of older adults through nurses’ career self-reliance.